Increasing incidence and improved survival in ANCA-associated vasculitis—a Danish nationwide study. Issue 1 (12th December 2020) - Nelveg-Kristensen, Karl Emil; Szpirt, Wladimir; Carlson, Nicholas; McClure, Mark; Jayne, David; Dieperink, Hans; Gregersen, Jon Waarst; Krarup, Elizabeth; Ivarsen, Per; Torp-Pedersen, Christian; Egfjord, Martin
Abstract: Background: Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) carries a high risk of morbidity and mortality, with outcomes modified by treatment and an incidence that may be increasing. We examined temporal changes in incidence and mortality during 2000–15 using nationwide healthcare registries. Methods: Patients with incident AAV were identified using International Classification of Diseases Version 10 (ICD10) codes and grouped according to inclusion year (Period 1: 2000–04, Period 2: 2005–09, Period 3: 2010–15). Log link cumulative incidence regression adjusted for age, sex, renal function, cardiovascular disease, diabetes, hypertension and advanced disease severity were used to model survival. Results: We identified 1631 patients (52% male), corresponding to an incidence of 18.5 persons/million/year (Period 1: 15.1, Period 2: 18.5, Period 3: 21.4). The slope of incident serologic ANCA testing was steeper than that of AAV (P = 0.002). Mean [standard deviation (SD)] age was 60.2 (16.7) years and mean (SD) follow-up was 6.8 (4.7) years. A total of 571 (35%) patients died (5-year mortality of 22.1%), with an absolute risk ratio (ARR) for Periods 2 and 3 compared with Period 1 of 0.80 [confidence interval (CI) 0.65–0.98, P = 0.031] and 0.39 (CI 0.31–0.50, P < 0.001). About 274 patients developed end-stage renal disease (ESRD) [16.8% (Period 1: 23.3%, Period 2: 17.6%, Period 3: 12.5%)], with ARR decreasing over time: Period 2 0.61 (CI 0.42–0.87, P = 0.007) and Period 3 0.57 (CI 0.39–0.83, P = 0.003). The overall risk of death associated with ESRD or chronic kidney disease was 1.74 (CI 1.29–2.37, P < 0.001) and 1.58 (CI 1.21–2.07, P < 0.001). Conclusions: Incidence of ANCA testing and AAV diagnosis increased over the test period. Falls over time in mortality and ESRD risk may relate to earlier diagnosis and changes in treatment practice.